2016
DOI: 10.1016/bs.mie.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric Scattering Microscopy for the Study of Molecular Motors

Abstract: Our understanding of molecular motor function has been greatly improved by the development of imaging modalities, which enable real-time observation of their motion at the single-molecule level. Here, we describe the use of a new method, interferometric scattering microscopy, for the investigation of motor protein dynamics by attaching and tracking the motion of metallic nanoparticle labels as small as 20 nm diameter. Using myosin-5, kinesin-1, and dynein as examples, we describe the basic assays, labeling str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“…1B). MTs were detected label-free, as expected (35)(36)(37), and tubulin-bound gold nanoparticles (tubulin-gold) appeared as points of high contrast (Fig. 1C).…”
Section: Monitoring Individual Tubulins Within Growing Microtubules Wsupporting
confidence: 68%
See 1 more Smart Citation
“…1B). MTs were detected label-free, as expected (35)(36)(37), and tubulin-bound gold nanoparticles (tubulin-gold) appeared as points of high contrast (Fig. 1C).…”
Section: Monitoring Individual Tubulins Within Growing Microtubules Wsupporting
confidence: 68%
“…We combined two recently introduced technologies, recombinant tubulin(32) and interferometric scattering microscopy (iSCAT) (33)(34)(35)(36), to make single-molecule observations of individual tubulin dimers binding to growing MT tips. We first generated a homogenous population of S. cerevisiae tubulin biotinylated through a C-terminal KCK epitope (tubulin-KCK) on the β-subunit (Tub2) ( Fig.…”
Section: Monitoring Individual Tubulins Within Growing Microtubules Wmentioning
confidence: 99%
“…Monitoring Individual Tubulins Within Growing MTs by iSCAT. We combined two recently introduced technologies, recombinant tubulin (32) and iSCAT (36)(37)(38)(39), to make single-molecule observations of individual tubulin dimers binding to growing MT tips. We first generated a homogenous population of Saccharomyces cerevisiae tubulin biotinylated through a C-terminal KCK epitope (tubulin-KCK) on the β-subunit (Tub2) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we overcome the longstanding challenge of single-molecule tubulin measurements by applying two recently developed technologies: recombinant tubulin (32)(33)(34)(35) and interferometric scattering microscopy (iSCAT) (36)(37)(38)(39). We first created biochemically homogeneous populations of tubulin subunits sparsely labeled with 20-nm gold nanoparticles.…”
Section: Significancementioning
confidence: 99%
“…We sought to resolve the stepping kinetics of individual KIF3A and KIF3C motor domains in homo-and heterodimeric motors and to determine the transport potential of the dimers under mechanical load. To accomplish this, we assayed motor activity using interferometric scattering (iSCAT) microscopy, a recent advance in light microscopy which has sufficient spatiotemporal precision to resolve single steps of a kinesin motor during processive runs (19)(20)(21)(22)(23), and optical trapping which reveals the motor performance under forces hindering and assisting plus-end directed motility (24)(25)(26)(27)(28)(29). We observed that the step dwell time distribution of KIF3AC is not a combination of the dwell time distributions observed for KIF3AA and KIF3CC and is adequately fit by a single exponential rate.…”
Section: Introductionmentioning
confidence: 99%